Current Molecular Biology and Therapeutic Strategy Status and Prospects for circRNAs in HBV-Associated Hepatocellular Carcinoma - Liao, Rui; Liu, Lei; Zhou, Jian; Wei, Xufu; Huang, Ping (Frontiers in Oncology, 2021)
Circular RNAs (circRNAs) are newly classified noncoding RNA (ncRNA) members with a covalently closed continuous loop structure that are involved in immune responses against hepatitis B virus (HBV) infections and play important biological roles in the occurrence and pathogenesis of HCC progression. The roles of circRNAs in HBV-associated HCC (HBV-HCC) have gained increasing attention. Substantial evidence has revealed that both tissue and circulating circRNAs may serve as potential biomarkers for diagnostic, prognostic and therapeutic purposes. So far, at least four circRNA/miRNA regulatory axes such as circRNA_101764/miR-181, circRNA_100338/miR-141-3p, circ-ARL3/miR-1305, circ-ATP5H/miR-138-5p, and several circulating circRNAs were reported to be associated with HBV-HCC development. Notably, TGF/SMAD, JAK/STAT, Notch and Wnt/β-catenin signaling pathways may play pivotal roles in this HBV-driven HCC via several circRNAs. Moreover, in non-HBV HCC patients or HCC patients partially infected by HBV, numerous circRNAs have been identified to be important regulators impacting the malignant biological behavior of HCC. Furthermore, the role of circRNAs in HCC drug resistance has become a focus of research with the aim of reversing chemoresistance and immune resistance. Herein, we review the molecular biology of circRNAs in HBV-HCC and their potential in therapeutic strategies.